2020
DOI: 10.3390/pharmaceutics12020194
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor-T-Cell Therapy for B-Cell Hematological Malignancies: An Update of the Pivotal Clinical Trial Data

Abstract: Chimeric antigen receptor (CAR)-T-cell therapy is an innovative form of adoptive cell therapy that has revolutionized the treatment of certain hematological malignancies, including B-cell non-Hodgkin lymphoma (NHL) and B-cell acute lymphoblastic leukemia (ALL). The treatment is currently also being studied in other B-cell neoplasms, including multiple myeloma (MM) and chronic lymphocytic leukemia (CLL). CD19 and B-cell maturation antigen (BCMA) have been the most popular target antigens for CAR-T-cell immunoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 83 publications
(167 reference statements)
0
41
0
1
Order By: Relevance
“…Since our in vivo studies were conducted in immunedeficient NSG-SGM3 mice, we do not know whether the in vitro safety or the in vivo toxicity is more likely to predict treatment outcomes in humans. 35 If clinical studies demonstrate that the benefits we observed treating human AML with CLL-1-CAR-IL15 T cells in mice are similar in patients, then TNFα antibody may need to be added to the repertoire of cytokine-neutralizing agents [54][55][56] required to ensure both safe and effective CAR T cell treatments. Combination of such antibodies with regulation of T cell expansion and survival with a clinically validated safety system such as described here using iC9 56 may be optimal.…”
Section: Discussionmentioning
confidence: 99%
“…Since our in vivo studies were conducted in immunedeficient NSG-SGM3 mice, we do not know whether the in vitro safety or the in vivo toxicity is more likely to predict treatment outcomes in humans. 35 If clinical studies demonstrate that the benefits we observed treating human AML with CLL-1-CAR-IL15 T cells in mice are similar in patients, then TNFα antibody may need to be added to the repertoire of cytokine-neutralizing agents [54][55][56] required to ensure both safe and effective CAR T cell treatments. Combination of such antibodies with regulation of T cell expansion and survival with a clinically validated safety system such as described here using iC9 56 may be optimal.…”
Section: Discussionmentioning
confidence: 99%
“…CAR T-cell therapy is an innovative form of adoptive cell therapy that has revolutionized the treatment of certain hematological malignancies. 8 B-cell maturation antigen (BCMA), a highly plasma cell-selective protein expressed on malignant plasma cells of patients with multiple myeloma (MM), has appeared as a promising antigen to target, using a variety of immunotherapy treatments including CAR T-cells, for MM patients. 9 It will likely result in increased acquired deficiencies in humoral immunity and subsequent infections in persons with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, chimeric antigen receptor modified T cells (CAR-T cells) have appeared in recent years as a successful immunotherapy for certain hematological malignancies [ 84 ]. However, some patients treated with CAR-T cells relapse, which is partially caused by a lack of functional persistence following treatment administration [ 221 ]. As the effectiveness of CAR-T cell therapy is dependent on the fitness of the patients’ T cells from which they are derived [ 222 ], the lack of sustained functional capacity of CAR-T cells could be due to the inflated levels of T cell senescence observed in cancer patients [ 107 ].…”
Section: Clinical Relevance Of Senescence In Immunotherapy: a Balamentioning
confidence: 99%